2014
DOI: 10.1016/j.jdent.2014.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Extracts of irradiated mature human tooth crowns contain MMP-20 protein and activity

Abstract: Objectives We recently demonstrated a significant correlation between enamel delamination and tooth-level radiation dose in oral cancer patients. Since radiation can induce the synthesis and activation of matrix metalloproteinases, we hypothesized that irradiated teeth may contain active matrix metalloproteinases. Materials and Methods Extracted teeth from oral cancer patients treated with radiotherapy and from healthy subjects were compared. Extracted mature third molars from healthy subjects were irradiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
16

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 23 publications
0
37
0
16
Order By: Relevance
“…In this context, a recently published study demonstrated a higher expression of matrix metalloproteinase-20, also called enamelysin, in the dentin-enamel junction surroundings of in vitro irradiated teeth. The proteolytic activity of matrix metalloproteinase-20 could also degrade the complex structure of noncollagenous proteins such as amelogenin and ameloblastin located in the enamel organic matrix in interprismatic enamel, leading to enamel delamination and contributing to the etiology of radiation-related caries [McGuire et al, 2014b].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a recently published study demonstrated a higher expression of matrix metalloproteinase-20, also called enamelysin, in the dentin-enamel junction surroundings of in vitro irradiated teeth. The proteolytic activity of matrix metalloproteinase-20 could also degrade the complex structure of noncollagenous proteins such as amelogenin and ameloblastin located in the enamel organic matrix in interprismatic enamel, leading to enamel delamination and contributing to the etiology of radiation-related caries [McGuire et al, 2014b].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro radiation exposure was done at a cancer treatment center (Kansas City Cancer Center, Kansas City, KS, USA) using a linear accelerator 2100iX (Varian Medical Systems, Palo Alto, CA, USA) with an energy of 6 MV photons. Additionally, another group of extracted teeth (n = 5; in vivo-irradiated; IRB13-143), described previously in detail, was also collected (McGuire et al, 2014a). Briefly, the tooth-level radiation dose was > 60 Gy during treatment for oral cancer from donors > 40 yr old, and the teeth were extracted ≥ 2 yr post-radiotherapy.…”
Section: Materials and Methods Collection Of Teeth And Preparationmentioning
confidence: 99%
“…These findings suggest a radiogenic effect on tooth structure with increasing radiation dose to the tooth. To better understand radiotherapy-induced DEJ instability leading to dentition breakdown, our group is focused on characterizing the structure, properties, and biochemical composition (Dusevich et al, 2012;Xu et al, 2012;McGuire et al, 2014b) of the DEJ, as well as postradiation changes (McGuire et al, 2014a).…”
mentioning
confidence: 99%
“…For root dentin, with higher organic content than enamel, it was the most affected by gamma radiation compared to enamel ad coronary dentin, as demonstrated in the literature [6][7][8].…”
Section: Cutting and Obtaining Blocks Of Dental Enamel And Root Dentinmentioning
confidence: 72%